Application of Plastic Ball Modification through Teams Games Tournament Learning Model to Improve Volleyball Lower Passing in Class V MI Ath-Thohariyah - Iqbal Gunawan; Ani Kurniawati (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
This study aims to determine the effect of applying modified plastic ball learning media on volleyball underhand passing at MI Ath-Thohariyah. Experimental research is the methodology employed in this study. employing a single kind of experimental study, namely the one group pretest-posttest pre-experimental design. The pupils in class V of MI Ath-Thohariyah will be the population employed in this study. A total of 25 male students from class V MI Ath-Thohariyah made up the sample for this study, which used non-probability sampling. The pre-test average was 49.36 after receiving a plastic ball modification therapy utilizing the Teams Games Tournament technique for 12 meetings, and the post-test score was 82.04, indicating that the rise was 32.68, according to the t test results. Furthermore, the t-count value is 23.43 according to the t-test. 1.71 is the t-table value at a significant level of 5% and a df of 24. It is therefore possible to state that there is a significant increase in the score of the lower passing ability results by being given a plastic ball modification using the teams games tournament method for 12 meetings because t-count > t-table (23.43 > 1.71) and the significance value is smaller than 0.05 (0.00 < 0.05).